1993
DOI: 10.1159/000126484
|View full text |Cite
|
Sign up to set email alerts
|

Feed Restriction in Prepubertal Lambs: Effect on Puberty Onset and on in vivo Release of Luteinizing-Hormone-Releasing Hormone, Neuropeptide Y and Beta-Endorphin from the Posterior-Lateral Median Eminence

Abstract: The exact nature of the interaction between energy balance and reproduction is still elusive. Theoretically, nutrition-related variables must reach the hypothalamic luteinizing-hormone-releasing hormone (LHRH) network and/or its neuronal inputs, to alter plasma luteinizing hormone (LH) and therefore reproductive activity. In an attempt to assess the potential mechanism of such interaction at the median eminence (ME) level, the area of hypophysiotropic LHRH neuronal terminals and release, we used a decreased ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 31 publications
2
17
0
Order By: Relevance
“…The increase in 13-EP release was observed each day in the late morning and early afternoon and was followed by an increase in LHRH release. The pulsatile nature of the portal blood LHRH and P-EP levels is consistent with the data obtained from ewe portal blood samples [26-281, from rat and ewe median eminence push-pull perfusates [11,12,24,29], and from in vitro perfusion of rat hypothalamic tissues [30]. The early morning increase in P-EP release prior to the preovulatory LHRH release on the day of proestrus has been previously documented in rats [18].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The increase in 13-EP release was observed each day in the late morning and early afternoon and was followed by an increase in LHRH release. The pulsatile nature of the portal blood LHRH and P-EP levels is consistent with the data obtained from ewe portal blood samples [26-281, from rat and ewe median eminence push-pull perfusates [11,12,24,29], and from in vitro perfusion of rat hypothalamic tissues [30]. The early morning increase in P-EP release prior to the preovulatory LHRH release on the day of proestrus has been previously documented in rats [18].…”
Section: Discussionsupporting
confidence: 85%
“…Studies using intra-cranial administration of P-EP or the opiate antagonist naloxone into the discrete areas of the hypothalamus and using measurement of the levels of immunoreactive 3-EP and of the 3-EP precursor proopiomelanocortin (POMC) mRNA in the hypothalamus revealed that the opioid peptide regulates LHRH secretion by acting both at the preopticanterior hypothalamus and the median eminence during the rat estrous cycle [8][9][10][11][12]. In accordance with this is the anatomical evidence that the P-EP immunoreactive neurons have direct contact with the LHRH neurons in the hypothalamus and that the opiate receptors are in proximity to LHRH-containing neurons in the hypothalamus [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…76]. There is also a reduction of GnRH release into the hypophysial portal vessels of the feed-restricted ewe [77], although some studies have not noted significant changes in GnRH release, or only a decrease in GnRH pulse amplitude in underfed ewes [72,73,78]. GnRH biosynthesis at the lev el of the POA also remains unchanged in such animals [53].…”
Section: Npy Gal Underfeeding and The Secretion O F Gonadotropins mentioning
confidence: 99%
“…Global feed restrictions increase the expression of NPY mRNA in the ARC nucleus of ovariectomised ewe lambs (Mc Shane et al, 1993), but the release of NPY within the median eminence did not change (Prasad et al, 1993). In ovariectomised The role of exogenous ghrelin in the regulation of neuropeptide Y (NPY) neuronal system in the hypothalamus of intact lambs has not been yet determined.…”
Section: Introductionmentioning
confidence: 99%